La elección del género de vida en la Enéada III4 (15) de Plotino - Tonelli, Malena (Pontificia Universidad Católica del Perú, 2025)
“The Choice of Life in Plotinus’ Ennead III4 (15)”. In Ennead III4 (15) Plotinus incorporates certain passages from Platonic dialogues that discuss the concept of the daimon. His analysis focuses on the soul –particularly the individual one– and how conduct should be understood. Although Porphyry gave this treatise the title On our allotted daimon, taken from the Phaedo, Plotinus’ starting point is rather the soul’s capacity, prior to its union with the body, to choose the daimon that will lead it to a particular type of life, as shown by the Myth of Er in the Republic. As can be seen, the responsibility lies in this choice and the body appears to play no role in shaping the conduct of the individual subject. An unintended consequence of this view is that the embodied soul, once the daimon has been chosen, would be unable to deteriorate or improve. Therefore, as I understand it, learning, the pursuit of virtue, and perhaps even the philosophical endeavor itself would become meaningless. In this paper I offer a close analysis of select passages from III4 (15) with the aim of examining the problem of the soul’s choice and decision-making, as well as its interaction with the body.

En la Enéada III4 (15), Plotino integra pasajes de diálogos de Platón en los que se encuentra la noción de dáimon. El análisis se concentra en el alma –especialmente la individual– y en el modo en que debe comprenderse la conducta. Ahora bien, a pesar de que Porfirio lo tituló “Sobre el dáimon que hemos recibido en suerte”, tomando el Fedón, Plotino parte de la capacidad que tiene el alma –antes de la combinación con el cuerpo– de elegir al dáimon que la conducirá a un género de vida o a otro, a la luz del mito de Er de la República. Como se ve, la responsabilidad recae en esa elección, y el cuerpo parece no tener lugar en la conducta del individuo. La consecuencia indeseada sería que, una vez elegido el dáimon, para el alma encarnada no es posible ni empeorar ni mejorar; por lo cual, según entiendo, el aprendizaje, la aspiración de alcanzar la virtud –acaso la tarea filosófica misma–, no tendría razón de ser. En este trabajo, me propongo ofrecer un acotado análisis de algunos pasajes de III4 (15) con vistas a examinar el problema de la elección y decisión del alma, y su comercio con el cuerpo.
The Choice of Life in Plotinus’ Ennead III4 (15)
Keywords: Soul; III4; Daímon; Responsibility; Plotinus; Alma; III4; Daímon; Responsabilidad; Plotino; https://purl.org/pe-repo/ocde/ford#6.03.01